Accessibility in Online User Testing - Oncins, Estella (Journal of Audiovisual Translation, 2021)
The current COVID-19 crisis has revealed the crucial role of online communication technologies in providing unique opportunities to carry out qualitative research in online user-based testing. The ability to provide a shared common space for participants living in different parts of the world and to record discursive data in text format accurately, makes these tools crucial in gathering qualitative data for research studies (Turney & Pocknee, 2005). Although the accessibility of the online communication platforms is improving, they still present significant challenges for all users, especially when running synchronous meeting sessions with participants in remote settings (Dodds & Hess, 2020).